PERAN UNITED NATIONS POPULATION FUND (UNFPA) DALAM ADVOKASI KESEHATAN REPRODUKSI REMAJA PEREMPUAN DI INDONESIA (2018-2023) - Waskitoningtyas, Kinanthi Wahyu; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study examines the role of the United Nations Population Fund (UNFPA) in addressing reproductive health issues among adolescent girls in Indonesia, including risks of early pregnancy, limited access to health services, gender-based violence, and inadequate socialization. Using qualitative descriptive methods and secondary data collection through literature review of annual reports, documents, and official publications from WHO, UNFPA, the Indonesian Ministry of Health, and academic articles related to the BERANI Program (2018-2023), the research applies Clive Archer's theory of International Organizations' Roles. The research findings indicate that UNFPA Indonesia has contributed to the improvement of adolescent reproductive health indicators, such as the decline in child marriage rates from 11.2% in 2018 to approximately 10% in 2022, as well as increased participation of adolescent girls in education and health. The analysis results explain that UNFPA Indonesia serves as an effective instrument providing technical and financial resources, with the BERANI Program advocating for child marriage policies, strengthening sexuality education in schools, and supporting the establishment of youth-friendly clinics (UNALA). This study recommends strengthening cross-sector collaborations to expand the program's impact and reduce challenges in reproductive health interventions. Keywords: Teen reproductive health, UNFPA Indonesia, BERANI Programme